(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: We described demographic and clinical characteristics and evaluated changes in vision-related quality of life alongside visual outcomes in patients with open-globe ocular trauma. Participants and design: We conducted a prospective observational study at the Vietnam National Eye Hospital from June 2023 to June 2024 and analyzed 509 patients (636 eyes). Visual outcomes and vision-related quality of life were measured using best-corrected visual acuity and the NEI VFQ-25 at two time points. Results: The mean age was 35.13 ± 8.87 years and 67.6% were male. Mechanisms included penetrating injury (62.3%), intraocular foreign body (22.0%), and blunt trauma (15.7%). Lesions comprised globe laceration (40.9%), globe rupture (34.7%), perforating injury (2.4%), and intraocular foreign body (22.0%). Complications included relative afferent pupillary defect (36.0%), endophthalmitis (21.7%), and retinal detachment (25.5%). Visual acuity improved significantly: eyes ≥ 20/40 increased from 12.6% to 42.1%; eyes < 20/400 decreased from 28.5% to 8.0%; no light perception decreased from 29.1% to 9.4% (p < 0.0001). NEI VFQ-25 scores increased across all 12 domains (p < 0.05); the composite score increased from 59 to 69.2 (p = 0.01). Conclusion: Care at the national referral center improved both objective visual acuity and vision-related quality of life. Combining best-corrected visual acuity with a multidomain patient-reported instrument provided a more comprehensive appraisal of post-operative recovery.